A hysteretic model for self-centering precast concrete piers with varying shear-slip between segments. (1st June 2019) - Yang, Cancan; Okumus, Pinar; Ren, Ruolong
Highlights: Segmental, self-centering piers were tested under static and rapid cyclic loads. Segmental interface friction properties were obtained from tests. A hysteretic model is proposed to study varying shear-slip and post-tension. Lower friction increases energy dissipation but lowers stiffness, self-centering. Higher post-tension increases base shear and may decrease peak displacement. Abstract: Self-centering, precast, post-tensioned concrete, bridge columns can provide low-damage under earthquake loading and accelerated bridge construction. These columns can also be designed so that shear-slip occurs between precast segments to provide energy dissipation. This paper, first, presents experimental results of large-scale testing of pier specimens that can self-center and undergo shear-slip under cyclic lateral loading. In these tests, segment interface properties, which control shear-slip, changed as the silicone layer placed between each segment degraded during testing. Specimens with fresh silicone had more energy dissipation, lower stiffness, and higher residual displacements compared with the ones with degraded silicone. A hysteretic model is created to predict the global load-displacement behavior of piers under lateral loading by superimposing self-centering and shear-slip responses. Shear-slip measurements under both quasi-static and rapid cyclic tests were used to characterize the interface frictional properties to be used in hysteretic modeling. Friction coefficients of segment interfaces were also investigated under varying accumulative displacement, normal force, and shear-slip velocity. The proposed hysteretic model is validated using the experimental results. A parametric study was performed using the established hysteretic model to investigate the influence of friction properties of interface materials and initial post-tension forces on the seismic response. The results show that interface materials with lower friction coefficient will lead to enhanced energy dissipation, lower stiffness, and smaller self-centering capability. Selecting lower initial post-tension force decreases the stiffness. Finally, incorporating the hysteretic model in the Capacity-Demand-Diagram method, seismic response of piers with varying properties was predicted. The increase in friction coefficient and initial post-tension force consistently increases the maximum base shear demand. Increasing initial post-tension force decreases the peak displacement in most cases. Increasing friction coefficient can either increase or decrease the peak displacement.